P77Specific consideration when interpreting the hypertrophy response to pressure overload in C57BL/6NTac and C57BL/6J mice. (15th July 2014) - Zi, M; Stafford, N; Prehar, S; Shaheen, M; Oceandy, D; Neyses, L; Cartwright, E
Abstract: Purpose: Transverse aortic constriction (TAC) has been extensively used as a cardiac stress in genetically modified mice to investigate the molecular mechanisms of cardiac hypertrophy. But the hypertrophic response to TAC can be significantly influenced by the time course of TAC, the age and the genetic background of the mice. The International Knockout Mouse Consortium has selected to use the C57BL/6NTac mouse strain to generate null alleles for all mouse genes; however, we have found a range of baseline cardiac phenotypic differences between this substrain and the commonly used C57BL/6J substrain. Therefore, we have assessed the optimal conditions to induce cardiac hypertrophy by TAC in the C57BL/6NTac strain, and have determined whether the hypertrophic response to TAC is different in these two C57BL/6 substrains. Methods: To establish the optimal conditions for TAC-induced hypertrophy in the C57BL/6NTac substrain, 8, 10 and 12-week old mice were subjected to TAC and monitored by echocardiography. Cardiac function was found to significantly deteriorate in 10-12 week old mice after 2 weeks, while 8-week old mice developed hypertrophy after 2 weeks and then reduced cardiac function after 5 weeks. Therefore, 2-week TAC in 8 week old mice was used to further study the hypertrophic response in the two C57BL/6 substrains. Echocardiography, conscious ECG, cardiac haemodynamic assessment, histology, and real-time PCR were conducted to evaluate cardiac function, hypertrophy, fibrosis, and the expression of hypertrophy markers. Results: Cardiac hypertrophy evaluated by heart weight to tibia length ratio (HW/TL) was highly variable in C57BL/6J mice, but this reflected the variation in aortic arch dimension as assessed by echocardiography. When comparing the response to the hypertrophic stimulus, C57BL/6NTac demonstrated greater hypertrophic growth as evaluated by HW/TL, cardiomyocyte cell surface area, and expression of BNP (all p<0.05). Cardiac remodelling such as fibrosis was also more extensive. This exacerbated hypertrophic growth was associated with increased QRS duration (19.33±2.76 vs. 15.29±0.64 ms, p=0.01), QTc interval and multiple ventricular arrhythmias in C57BL/6NTac mice. Conclusion: There are clear differences in the response to pressure overload in widely used C57BL/6 substrains. C57BL/6J mice were found to have a large variation in aortic structure which is reflected in the variable hypertrophic response; whilst the C57BL/6NTac substrain has a consistently exacerbated hypertrophic response. It is therefore essential to consider these distinct phenotypic differences when interpreting data.